Auxiliary proteins promote modal gating of AMPA‐ and kainate‐type glutamate receptors. (April 2014) - Zhang, Wei; Devi, Suma Priya Sudarsana; Tomita, Susumu; Howe, James R.
Abstract The gating behavior of α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) and kainate receptors is modulated by association with the auxiliary proteins: transmembrane AMPA receptor regulatory proteins (TARPs) and neuropilin tolloid‐like (Netos), respectively. Although the mechanisms underlying receptor modulation differ for both AMPA and kainate receptors, association with these auxiliary subunits results in the appearance of a slow component in the decay of ensemble responses to rapid applications of saturating concentrations of glutamate. We show here that these components arise from distinct gating behaviors, characterized by substantially higher open probability (Popen), which we only observe when core subunits are associated with their respective auxiliary partners. We refer to these behaviors as gating modes, because individual receptors switch between the low‐ and high‐Popen gating on a time‐scale of seconds. At any given time, association of AMPA and kainate receptors with their auxiliary subunits results in a heterogeneous receptor population, some of which are in the high‐Popen mode and others that display gating behavior similar to that seen for receptors formed from core subunits alone. While the switching between modes is infrequent, the presence of receptors displaying both types of gating has a large impact on both the kinetics and amplitude of ensemble currents similar to those seen at synapses.